Fumigant Components from the Essential Oil of Evodia Rutaecarpa Hort Unripe Fruits - Zhi Long Liu; Shu Shan Du (E-Journal of Chemistry)
Essential oil of chinese medicinal herb, Evodia rutaecarpa unripe fruits was found to possess insecticidal activity against maize weevils, Sitophilus zeamais and red flour beetles Tribolium castaneum. The essential oil of E. rutaecarpa was obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 38 components of the essential oil were identified. The principal compounds in E. rutaecarpa essential oil were β-myrcene (17.7%), (Z)-β-ocimene (14.8%), α-phellandrene (14.7%), γ-terpinene (6.4%), linalool (5.7%) and β-thujene (5.1%). Bioactivity-guided chromatographic separation of the essential oil on repeated silica gel columns led to isolate three volatile components (β-myrcene, β-ocimene and α-phellandrene) from the essential oil. α-Phellandrene was strongest fumigant against S. zeamais adults, T. castaneum adults and T. castaneum larvae with LC50 values of 15.61, 19.78 and 47.96 mg/L air, respectively. β-Myrcene and β-ocimene also possess fumigant activity against the two species of insects but weaker fumigant activity than the crude essential oil.